1996
DOI: 10.1002/(sici)1097-0185(199607)245:3<459::aid-ar2>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical studies on the expression and estrogen dependency of EGF and its receptor and C-fos proto-oncogene in the uterus and vagina of normal and neonatally estrogen-treated mice

Abstract: Background The final target cell response to estrogen is dependent not only on the estrogen receptor, but also on autocrine/paracrine interactions with growth factors (e.g., EGF) and proto‐oncogenes (e.g., c‐fos). Because neonatal estrogen treatment results in permanent changes in the female mouse genital tract (permanent vaginal cornification, cervical adenosis and tumors, changed growth control mechanisms in uterus), it was of interest to study possible acute and permanent effects of such treatment on distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…EGF and EGF mRNA levels are increased by estrogen in the mouse uterus (DiAugustine et al, 1988;Falck and Forsberg, 1996). The TGF-α mRNA level is also increased by estrogen in the adult ovariectomized rat uterus (Borgundvaag et al, 1992) and in the immature mouse uterus (Nelson et al, 1992).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…EGF and EGF mRNA levels are increased by estrogen in the mouse uterus (DiAugustine et al, 1988;Falck and Forsberg, 1996). The TGF-α mRNA level is also increased by estrogen in the adult ovariectomized rat uterus (Borgundvaag et al, 1992) and in the immature mouse uterus (Nelson et al, 1992).…”
Section: Discussionmentioning
confidence: 96%
“…Immunoreactive EGF has been localized in the neonatal and adult mouse uterine stromal cells (Falck and Forsberg, 1996). TGF-α and its mRNA are also detected in both uterine epithelial cells and stromal cells (Tamada et al, 1991).…”
Section: Introductionmentioning
confidence: 97%
“…EGF and insulin-like growth factor (IGF)-I stimulate cell proliferation in immature mouse uterine and vaginal epithelial cells in vitro (Tomooka et al 1986, Iguchi et al 1987, Shiraga et al 1997. Because estrogen stimulates uterine epithelial cell proliferation (McCormack & Glasser 1980, Quarmby & Korach 1984 and expression of EGF, IGF-I, heparin-binding EGF-like growth factor, transforming growth factor (TGF)-and EGF-R in the reproductive tracts of mice and rats, these growth factors may mediate the estrogen-induced proliferative and differentiative responses in rodent reproductive tracts (Murphy et al 1987, DiAugustine et al 1988, Nelson et al 1991, Beck & Garner 1992, Ignar-Trowbridge et al 1992, Kapur et al 1992, Das et al 1994, Sahlin et al 1994, Zhang et al 1994, Falck & Forsberg 1996, Hom et al 1998. In the fetal reproductive tract, expression of EGF-R in mice (Bossert et al 1990), and EGF, TGFand IGF-I in rats (Koike & Noumura 1993, Kanno et al 1994, Gu et al 1999) was reported.…”
Section: Discussionmentioning
confidence: 99%
“…Distinct alterations in gene expression following neonatal DES exposure have been reported for EGF, EGF receptor, c-fos, c-jun, c-myc, bax, and bcl-2. [57][58][59] Although further studies will be required, neonatal estrogenic exposure might affect such genes, and induce carcinomas independently of surrounding stromal cells in adult mice.…”
Section: Discussionmentioning
confidence: 99%